2015
DOI: 10.4238/2015.july.27.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of progenies from the fifth reciprocal recurrent selection cycle in maize

Abstract: ABSTRACT. The objective of this study was to evaluate the performance of 119 full sib progenies of the fifth cycle of reciprocal recurrent selection (RRS) derived from of Universidade Federal de Lavras maize breeding program. The experiment was carried out in an 11 x 11 triple lattice design at two locations (Lavras, Lambari). The plots consisted of two rows of 3 m, with four plants per 1 m and 0.60 meters of spacing between lines. The grain yield was obtained as kg/plot through weighing of husked ears. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…The expected selection gain, based on a selection intensity of 10%, was 14.07%, similar to the value reported by Alves et al (2015) (16%), indicating that reciprocal recurrent selection was effective. Thus, high values of heritability result in high gains due to selection reliability.…”
Section: Resultssupporting
confidence: 84%
“…The expected selection gain, based on a selection intensity of 10%, was 14.07%, similar to the value reported by Alves et al (2015) (16%), indicating that reciprocal recurrent selection was effective. Thus, high values of heritability result in high gains due to selection reliability.…”
Section: Resultssupporting
confidence: 84%
“…Data concerning ears plant -1 expressed highly significant differences among the half sib recurrent families of maize population CZP-132011. The current findings are in line with Noor et al (2010) who also noted significant (P<0.01) differences among half sib recently families of maize Varity Pahari for plant and ear height, while Alves et al (2015) reported significant differences in fifth recurrent cycle in maize progenies for ears plant -1 . After one cycle of recurrent selection the gain cycle -1 for ears plant -1 was 3.26%.…”
Section: Ears Plant -1supporting
confidence: 92%